Диаграмма мартенситных превращений в сплавах на основе никелида титана, легированных серебром - Байгонакова, Гульшарат Аманболдыновна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIII Международной конференции студентов, аспирантов и молодых ученых, Россия, Томск, 26-29 апреля 2016 г.)
Results of research of martensite transformations in TiNi-based alloys doped by 0.1-1.5 at. %o Ag are presented. Temperature dependences of curves of electrical resistivity are received and characteristic temperatures of martensite transformations on the basis of the analysis of these dependences in the studied alloys are determined. The diagram of martensite transformations in system (Ti, Ni, Mo, Fe)Ag depending on concentration is constructed on the received values of characteristic temperatures.